'Changing the context': Tackling discrimination at school and in society. (March 2015) - Howarth, Caroline; Andreouli, Eleni
Highlights: Schools can play a key role in reducing discrimination and so act as agents of change. Research informed by Social Representations Theory allows a focus on barriers to change and social mechanisms for social and contextual change. We need to examine interconnection between the macro socio-political context, the meso local context and the micro context of social encounters. Best practice models should be located in particular contexts and so address local issues and challenges. Research needs also to move beyond education to address the causes of discrimination in local and broader socio-political contexts. Abstract: In this paper we propose a social psychological framework for studying the role of schools in promoting positive intercultural relations. We draw on data from schools in England where addressing issues of cultural diversity is a key aim of educational practice. We focus specifically on the role of social context in educational activities that tackle discrimination. We consider the socio-political context, local community context, and immediate school context from a social representations theory perspective. Using data from interviews with staff and focus groups with students in schools from three very different localities, we show that the socio-political context may limit schools' ability to promote positive intercultural relations but also that it is possible for schools to promote broader change from the bottom-up, acting as agents of change at a societal level, i.e. in terms of changing the local and broader societal contexts in which they are located.